2014
DOI: 10.1017/s0967199414000173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of jacalin and follicle-stimulating hormone onin vitrogoat primordial follicle activation, survival and gene expression

Abstract: This study aims to investigate the effects of jacalin and follicle-stimulating hormone (FSH) on activation and survival of goat primordial follicles, as well as on gene expression in cultured ovarian tissue. Ovarian fragments were cultured for 6 days in minimum essential medium (MEM) supplemented with jacalin (10, 25, 50 or 100 μg/ml - Experiment 1) or in MEM supplemented with jacalin (50 μg/ml), FSH (50 ng/ml) or both (Experiment 2). Non-cultured and cultured tissues were processed for histological and ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
3
0
1
Order By: Relevance
“…Several genes have been identified in follicular walls as biomarkers to understand the dynamics of follicular development. Among them GPx related to oxidative stress [64], KL indicative of follicular growth [65]; cyclin B1 and HAS2 indicative of progression of oocyte maturation [66]. We observed that after the IVM of COCs from secondary follicles, the follicular walls (granulosa and theca cells) expressed similar transcript levels.…”
Section: Discussionmentioning
confidence: 89%
“…Several genes have been identified in follicular walls as biomarkers to understand the dynamics of follicular development. Among them GPx related to oxidative stress [64], KL indicative of follicular growth [65]; cyclin B1 and HAS2 indicative of progression of oocyte maturation [66]. We observed that after the IVM of COCs from secondary follicles, the follicular walls (granulosa and theca cells) expressed similar transcript levels.…”
Section: Discussionmentioning
confidence: 89%
“…The tissues were cut into 5-μm sections, stained with hematoxylin–eosin and then examined by microscopy (Nikon, Tokyo, Japan; ×400 magnification). Follicles were classified as primordial (one layer of flattened or flattened and cuboidal granulosa cells around the oocyte), primary (one layer of cuboidal granulosa cells) or secondary (two or more layers of cuboidal granulosa cells around the oocyte) (Ribeiro et al , 2014), and as morphologically normal or atretic, according to the presence or absence of pyknotic nucleus, retracted oocyte, and/or disorganized granulosa cells detached from the basement membrane. To evaluate follicular activation, only morphologically normal follicles with a visible oocyte nucleus were recorded, and the proportion of primordial and growing follicles was calculated at day 0 (fresh control) and after 7 days of culture.…”
Section: Methodsmentioning
confidence: 99%
“…Assim, os autores demonstraram a importância fundamental da GAL-1 na tolerância materno-fetal e na sinergia entre GAL-1 e progesterona na manutenção da gestação. Ribeiro et al, (2015) investigaram o efeito de diferentes concentrações de uma lectina vegetal no desenvolvimento, maturação e fertilização de folículos, e verificaram que esta molécula estimula a ativação dos folículos e contribui para a manutenção da viabilidade embrionária, bem como exerce efeito na expressão de mRNA.…”
Section: Maureira Et Al (2020) Reportaram Aumento Da Fertilidade Devi...unclassified